Prolyl Hydroxylase Domain-Containing Protein 3 Gene Expression in Chondrocytes Is Not Essential for Bone Development in Mice - Weirong Xing (Cells, 2021)
We previously showed that conditional disruption of the Phd2 gene in chondrocytes led to a massive increase in long bone trabecular bone mass. Loss of Phd2 gene expression or inhibition of PHD2 activity by a specific inhibitor resulted in a several-fold compensatory increase in Phd3 expression in chondrocytes. To determine if expression of PHD3 plays a role in endochondral bone formation, we conditionally disrupted the Phd3 gene in chondrocytes by crossing Phd3 floxed (Phd3flox/flox) mice with Col2α1-Cre mice. Loss of Phd3 expression in the chondrocytes of Cre+; Phd3flox/flox conditional knockout (cKO) mice was confirmed by real time PCR. At 16 weeks of age, neither body weight nor body length was significantly different in the Phd3 cKO mice compared to Cre−; Phd3flox/flox wild-type (WT) mice. Areal BMD measurements of total body as well as femur, tibia, and lumbar skeletal sites were not significantly different between the cKO and WT mice at 16 weeks of age. Micro-CT measurements revealed significant gender differences in the trabecular bone volume adjusted for tissue volume at the secondary spongiosa of the femur and the tibia for both genotypes, but no genotype difference was found for any of the trabecular bone measurements of either the femur or the tibia. Trabecular bone volume of distal femur epiphysis was not different between cKO and WT mice. Histology analyses revealed Phd3 cKO mice exhibited a comparable chondrocyte differentiation and proliferation, as evidenced by no changes in cartilage thickness and area in the cKO mice as compared to WT littermates. Consistent with the in vivo data, lentiviral shRNA-mediated knockdown of Phd3 expression in chondrocytes did not affect the expression of markers of chondrocyte differentiation (Col2, Col10, Acan, Sox9). Our study found that Phd2 but not Phd3 expressed in chondrocytes regulates endochondral bone formation, and the compensatory increase in Phd3 expression in the chondrocytes of Phd2 cKO mice is not the cause for increased trabecular bone mass in Phd2 cKO mice.